IMPLEMENTASI PROGRAM TAHU PANAS (TAK TAKUT KEHUJANAN DAN TAK TAKUT KEPANASAN ) GUNA MERAHABILITASI RUMAH TIDAK LAYAK HUNI DI KOTA SURABAYA - Novia Silam Sari; Indah Murti; Dida Rahmadanik (Faculty of Social and Political Science, 2022)
Rehabilitating uninhabitable houses that are still scattered in the city of Surabaya by looking at what things often happen when the program is running well. from program implementers to beneficiaries who in this program work together in the implementation process. This research is descriptive qualitative research. The subjects of this study were the head of the rehabilitation section for uninhabitable houses, hot tofu program assistants in the field, and beneficiaries of the hot tofu program. The research instrument is the researcher himself. Data collection techniques are interview techniques, observation, and documentation. The data analysis technique used is the interactive analysis technique. The theory used in this study uses the opinion put forward by Van Meter Van Horn, which consists of six variables, namely policy size, and objectives, resources, characteristics of implementing agents, attitudes of implementers, inter-organizational communication and the socio-political environment. Based on the results of the research, it can be concluded that the implementation of the Hot Tofu program in rehabilitating uninhabitable houses in the city of Surabaya is going well even though there are several problems, namely, regarding human resources and material resources or materials used for building houses, this is what finally slowing down the development process so that it is often not in accordance with the scheduled time.